(untitled) (The Peerian Journal, 2024)
Cluster systems are increasingly recognized as vital tools for economic development in today’s world. They foster innovation, enhance competitiveness, and stabilize regional economies by creating a conducive environment for collaboration across industries, trade, and services. The study’s findings reveal how clusters contribute to economic growth, influence innovation processes, and bolster overall economic stability